(untitled) (Economics and region, 2022)
The basis of stability of any economic system is its structure and innovative model of economic development. Innovations generate positive structural changes in the economy, contribute to increasing the productivity of the economy, strengthen its ability to compete in the global environment with the economies of other countries and ensure sustainable growth rates in the long term. Since the Russian invasion, Ukraine’s economy has been functioning in war conditions. The losses of human capital, production and infrastructure potential, housing stock are colossal and enormous. Ukraine has an unprecedentedly high support of the entire civilized democratic world in confronting the Russian aggression and extremely high confidence of Ukrainian citizens in victory. This gives a chance not only to rebuild the destroyed, but also to carry out structural reforms and form an innovative model of development. The rating approach is widely used to assess the innovation potential, technological and innovation competitiveness of the country. The purpose of this article is to find out the place of Ukraine in the components of the subindices of the global innovation index, which reflect the potential of innovation and its main results, to identify the main problems and directions of their solution. The dynamics of Ukraine’s innovation profile by elements of subindices of the global innovation index, which is an objective indicator of the country’s ability and success in innovation, is studied. The analysis was carried out by five indicators of the sub-index of innovation expenditures and two indicators of the sub-index of innovation results. The positive tendency in the formation of innovative resources and innovative results is revealed, as well as the problems in the formation of an innovative model of economic development of Ukraine are identified. It is emphasized that the leaders of the world innovation development are countries with high per capita income. Based on the correlation analysis of data from 106 countries, it was concluded that both the level of the global innovation index and the level of the sub-index "Innovation performance" have a high impact on the level of income of the country.